PENGARUH LINGKUNGAN KERJA, KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA BPR WELERI MAKMUR) - Andre Septia Putra Suwarto, 13.05.51.0129; Muhaimin, . (Students' Journal of Economic and Management, 2017)
This study aims to examine and analyze the influence of Work Environment, Leadership and Work Motivation on Employee Performance. The object of research in this writing is BPR WELERI MAKMUR. The sampling technique in this research is using purposive sampling technique with the number of respondents 50 person.Analisis data used include the validity test with product moment, reliability test with alpha coefesien (Cronbrach Alpha), multiple regression analysis, t test to test and prove the research hypothesis . The results of the research are (1) The environment is not positive and insignificant to Employee Performance, (2) Leadership is not positive and significantly to Employee Performance, the stronger the leadership in employees will improve employee performance. (3) Motivation has a positive and significant impact on Employee Performance, the stronger motivation in the employees will improve employee performance. Keywords: Environment, Leadership, Motivation and Employee Performance.